TasybῙh Al-TamṡῙl Dalam Al-Qur’an: Analisis BalagᾹh Pada Surah Al-Kahfi Ayat 45 - Aritonang, Pebrina Yanti; Nurul Aulia Ersa Putri; Said Fahrezi; Harun al Rasyid (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
The Qur'an serves not only as a guide and source of law for Muslims but also as a literary masterpiece rich in linguistic beauty and balaghah (rhetorical) devices. One prominent form of balaghah in the Qur'an is tasybih al-tamthil, a simile that combines elements of tasybih (simile) and tamthil (analogy). This study aims to analyze tasybih al-tamthil in Surah Al-Kahf verse 45, which depicts the transient nature of worldly life through the analogy of rainwater that nourishes plants but eventually dries up and vanishes. This research employs a qualitative approach with content analysis, focusing on the balaghah analysis of the elements of tasybih al-tamthil, the figures of speech used, and the uslub (style) that supports the meaning of the simile. The findings reveal that the tasybih al-tamthil in this verse effectively conveys moral messages about the impermanence of worldly life, the fleeting nature of worldly pleasures, and the importance of remembering the afterlife. The use of figures of speech such as tasybih, isti'arah (metaphor), and kinayah (metonymy), along with careful word choice and sentence structure, strengthens the message and makes it more comprehensible and impactful for readers.